Global meta-analysis: Sparse tree cover increases grass biomass in dry pastures - Hernández-Salmerón, Ivan Raniero; Holmgren, Milena (Frontiers in Environmental Science, 2022)
Agricultural and ecological droughts, extreme heat and aridity have high impacts on livestock and pasture systems worldwide. Finding ways to adapt production systems and increase biomass under these new conditions is urgently needed. The availability of tree shade in these pastures could potentially ameliorate the impacts of warm weather. Yet, the effects of tree cover on the productivity of livestock rangelands are hotly debated. We performed a global meta-analysis to evaluate the effects of tree cover on grass biomass during contrasting seasons within the same system and along environmental gradients in tropical and temperate productive systems. We also assessed the levels of canopy density at which tree cover effects are observable. We observed that trees facilitate grass biomass during dry seasons, especially in the tropics and dry regions. These positive effects are more likely to occur at intermediate levels of evapotranspiration and irradiance. Our findings suggest that integrating trees in pastures might increase resilience of current livestock production systems to drier and warmer conditions.